The Effectiveness of Youth Training Programs in Curbing Unemployment Challenges in Uganda, Kabale District - Caroline Masiko Murezi; Akankwasa Alex; Moses Agaba Agaba (Goodwood Publishing, 2026)
Purpose: This study examines the effectiveness of youth training programs in Kabale District, Uganda, in addressing youth unemployment by equipping participants with marketable vocational, technical, entrepreneurial, and digital skills. Research Methodology: This study aims to determine the impact of these programs on employability and self-employment outcomes. Results: The analysis revealed a statistically significant but weak correlation between youth training and unemployment reduction (R = 0.317, R² = 0.100, p < 0.001), indicating that training explains approximately 10% of the variance in youth unemployment reduction. Vocational and technical programs, particularly in agriculture, ICT, and manufacturing, enhanced self-employment and entrepreneurial outcomes. Apprenticeships, internships, and hands-on learning further strengthen employability. Conclusions: Youth training programs positively influence employability and self-employment; however, their effect is limited. Complementary interventions, including access to finance, mentorship, and market-aligned training, are critical for sustained economic empowerment of women. Limitations: This study focused solely on training as a predictor of unemployment, excluding other socioeconomic factors, and the results were based on cross-sectional data from a single district, limiting generalizability. Contributions: This study provides evidence of the role of practical and entrepreneurial training in enhancing youth employability, offering insights for policymakers, NGOs, and educational institutions to optimize training design and support sustainable self-employment initiatives.